Experiences and Participatory Tools for Evaluation of Sustainability of Local Development Projects - Manrique, Silvina Magdalena (2015)
The Sustainability measuring is the strongest conducting force for the discussion of Sustainable Development (SD). A reliable measuring tool is a prerequisite for the assessment sustainability the processes, alternatives or systems. In Salta, Argentina, the bioenergy systems (energy systems based on biomass) could be implemented but it is necessary to define the baseline, in order to be able to monitor changes of the system as a whole. We build a simple and replicable methodology to estimate the level of sustainability ? from a framework locally and participating defined- of the Central Region (system or unit of analysis), and test how this level of sustainability could improve or worsen from the implementation of an bioenergy project. By means of a multidimensional analysis and the calculation of indexes, a current image diagnosis was obtained. This image was observed then in the potential future evolution, if bioenergy systems are implemented in the zone. The failings and the imbalances of the system are clearly identified, and therefore, allow focus towards the dimensions and variables that need to implement policies and corrective instruments. The methodology developed could be used to test other projects for the region or to be retrofitted with new variables in other regions.